Rydbergova blokada in enofotonski optični tranzistor - Lodrant, Katarina (Matrika, 2023)
The paper describes the basic mechanisms of a single photon transistor (switch) based on Rydberg atoms–atoms excited into states with a high quantum number n. First, Rydberg atoms are described and some important properties of such systems are considered. Next, interactions between Rydberg atoms (which result in the Rydberg blockade) are derived. The second part focuses on the mechanics of an optical transistor that exploits the properties of Rydberg atoms for achieving interactions between photons. The first ?$gate$? photon can be stored in the medium as an excitation which changes the optical properties for the oncoming ?$target$? photons. The gate photon can later be retrieved. Electromagnetically induced transparency and the principles of slow light are explained.
Keywords: interactions; interakcije; optični tranzistor; Rydberg atoms; Rydberg blockade; Rydbergova blokada; Rydbergovi atomi; single photon transistor